Calcineurin Inhibitors in the Treatment of Primary Focal Segmental Glomerulosclerosis: A Systematic Review and Meta-analysis of the Literature. Issue 1 (22nd February 2017) - Laurin, Louis-Philippe; Nachman, Patrick H.; Foster, Bethany J.
Purpose of review: Primary focal segmental glomerulosclerosis (FSGS) is the most common cause of nephrotic syndrome in adults. Glucocorticoids have been evaluated in the treatment of primary FSGS in numerous retrospective studies. Evidence suggesting a role for including calcineurin inhibitors (CNIs) in early therapy remains limited. The aim of this study was to systematically review the literature examining the efficacy of CNIs in the treatment of primary FSGS both as first-line therapy and as an adjunctive agent in steroid-resistant patients, with respect to remission in proteinuria and renal survival. Sources of information: PubMed and EMBASE were searched from inception to August 2014 for prospective controlled trials, and case-control and cohort studies. Findings: After systematically applying our inclusion criteria, a total of 152 titles and abstracts were identified. Six randomized controlled trials and 2 cohort studies were reviewed. Three randomized controlled trials compared CNIs with placebo or supportive therapy. The pooled relative "risk" of proteinuria remission associated with cyclosporine was 7.0 (95% confidence interval, 2.9-16.8) compared with placebo/supportive therapy. There was very low heterogeneity among these studies with an I -squared of 0%. Three studies compared CNIs with another immunosuppressive agent. All prospective trials were conducted in patients with primary FSGS deemed steroid-resistant. Limitations: The relatively small number of included studies and their heterogeneity with respect to treatment protocols, and possible publication bias, limit conclusions drawn from this systematic review. Implications: The efficacy of CNIs has been evaluated in steroid-resistant primary FSGS patients. There is no evidence supporting their role as first-line therapy. Further studies are needed to determine this role.